PENINGKATAN PENJUALAN PADA SHOWROOM JEPANG MOTOR GIANYAR MELALUI PELATIHAN GOOGLE ADS DAN META ADS: TRAINING AND GUIDANCE ON USING ADS AT SHOWROOM JEPANG MOTOR GIANYAR - M. Azman Maricar; Rifky Lana Rahardian; Made Doddy Adi Pranatha; Tegar Andhika Nugraha; Lulut Aji Aditya (Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
Jepang Motor Gianyar Showroom, a used motorcycle dealership, faces stagnant sales despite utilizing social media for marketing. A primary reason for this stagnation is the underutilization of digital advertising platforms like Google Ads and Meta Ads due to a lack of understanding regarding their implementation. This community service initiative aimed to enhance the showroom's capabilities in digital marketing, specifically through the effective use of Google Ads and Meta Ads. The provided solution encompassed a two-day program involving training and hands-on assistance, covering introduction, practical application, and evaluation of both advertising platforms. The two-day activity included pre-tests and post-tests to measure partner understanding, utilizing 10 statements with a 5-point Likert scale ranging from "strongly disagree" to "strongly agree." To assess the training's impact on sales, interviews were conducted before the training commenced and one month after its completion. The results indicate an approximate 50% increase in partner understanding, with pre-test scores rising from 40-50 to 75 in the post-test. Furthermore, the showroom's gross revenue also increased from IDR 21-30 million to over IDR 30 million per month following the implementation of digital advertising. While formal statistical analysis was not comprehensively conducted due to limitations in sample size, the observed increases in understanding scores and gross revenue demonstrate the effectiveness and positive impact of the intervention.